Digital media consumption preferences of adolescents and teachers as input for the design of digital educational resources on food, nutrition and healthy lifestyles of the Póngale Vida model - González-Urrutia, Rocío (2026)
Introduction: Nutritional Education must be adapted to digital consumption habits. Therefore, the digital media consumption preferences of students and teachers from three Professional Technical High Schools (CTP) in the Cantón of Golfito, were determined as a guiding input for the creation of digital content within the Póngale VidaⓇ model from the University of Costa Rica (UCR). Methodology: Quantitative, cross-sectional, and descriptive study conducted within the framework of the UCR-ED-3598 project. Population: Students and teachers from three CTPs, in the year 2022. Two digital questionnaires were developed to collect information on internet use, social media, digital content formats, and experience with virtual education, which were analyzed using descriptive statistics. Results: 79 teachers and 288 teenagers responded. Most people consume content using their mobile devices (96.5% and 75.9%), and the social media use ranges from three to four hours daily (30%). Students use more mobile data and consume content related to entertainment (music, movies, games, humor), both on websites and social networks. Health and nutrition topics are not among the top three preferred themes for both groups. Short videos are the favorite format. Conclusion: Health professionals must explore and learn new ways to work on health promotion with the teenager population and the teachers in charge. Nutritional education should be framed within E-Health, and M-learning should be used as one of its strategies, designing resources under the Mobile First philosophy-digital literacy- to reach this population through models such as Póngale VidaⓇ.